A fast iterative filtering decomposition and symmetric difference analytic energy operator for bearing fault extraction. (February 2021) - Xu, Yuanbo; Fan, Fan; Jiang, Xiangkui
Abstract: The fault vibration signals extracted from defective bearings are generally non-stationary and non-linear. Besides, such signals are extremely weak and easily buried by inevitable background noise and vibration interferences. Thus, the development of methods capable of detecting their hidden information in a fast and reliable way is of high interest in bearing fault detection. An alternative bearing fault extraction method based on fast iterative filtering decomposition (FIFD) and symmetric difference analytic energy operator (SD-AEO) is proposed in this work. The FIFD method performs excellently in suppressing mode mixing and produce a meaningful decomposition for a higher level of noise. More importantly, unlike other mode decomposition techniques, the FIFD has high computational efficiency, so we can speed up the calculations significantly. After decomposing the signal into a group of intrinsic mode functions (IMFs), a criterion based on the product of kurtosis and permutation entropy (PeEn) is proposed to choose the IMFs embedding richer bearing fault impulses. Subsequently, an enhanced demodulation technique, SD-AEO, is employed to detect the bearing fault signatures from the selected IMF. The simulated and real signals verify the efficiency of the proposed method. Highlights: A novel fast iterative filtering decomposition is used to decompose the signal with background noise and multiple components. An alternative demodulation method called symmetric difference analytic energy operator is presented, which is robust against the strong noise. An enhanced bearing fault detection method using the two techniques is presented is applied to bearing fault extraction.